TSE Diagnostics: Recent Advances in Immunoassaying Prions - Anja Lukan; Tanja Vranac; Vladka Čurin Šerbec (Clinical and Developmental Immunology)
Transmissible spongiform encephalopathies (TSEs) or prion diseases are a group of rare fatal neurodegenerative diseases, affecting humans and animals. They are believed to be the consequence of the conversion of the cellular prion protein to its aggregation-prone, β-sheet-rich isoform, named prion. Definite diagnosis of TSEs is determined post mortem. For this purpose, immunoassays for analyzing brain tissue have been developed. However, the ultimate goal of TSE diagnostics is an ante mortem test, which would be sensitive enough to detect prions in body fluids, that is, in blood, cerebrospinal fluid, or urine. Such a test would be of paramount importance also for screening of asymptomatic carriers of the disease with the aim of increasing food, drugs, and blood-derived products safety. In the present paper, we have reviewed recent advances in the development of immunoassays for the detection of prions.